Enrolment status of children in selected villages of Bangladesh: a survey on reopening of BRAC'S NFPE School - Khan, Md. Kaisar Ali; Mohsin, Md. (© BRAC, 2016)
1. Introduction 2. Background of the study 3. Methodology 4. General characteristics of the children, their households and village 5. Age-sex composition of the children 6. Households Status 7. BRAC group membership 8. Status of educational institutions 8. Enrolment Status 9. Possibilities of re-opening of NFPE / KK schools 10. Enrolment status and Socio- economic characteristics 11. Discussion and conclusion.